1996
DOI: 10.1021/jm960253w
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Characterization of Zinc Ejection from HIV Nucleocapsid Protein by Anti-HIV 2,2‘-Dithiobis[benzamides] and Benzisothiazolones

Abstract: HIV nucleocapsid protein (NCp7) has been suggested as a possible target for 2,2'-dithiobis-[benzamide] and benzisothiazolone agents that inhibit viral replication in infected cells (Rice et al. Science 1995, 270, 1194-1197). The solution behavior of these compounds and the mechanistic events leading to removal of Zn from HIV nucleocapsid protein in vitro has been studied by electrospray ionization mass spectrometry, 500 MHz one- and two-dimensional nuclear magnetic resonance spectroscopy, and circular dichrois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
108
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 23 publications
8
108
1
1
Order By: Relevance
“…First, it is interesting to note that only two molecules of the antiviral compound are required to completely inactivate one molecule of NCp7 as opposed to three molecules of disulfide based inhibitors (15,20,21) due to the lack of reactivity toward the aminoterminal zinc finger. Second, both the need for activation and the initial formation of a noncovalent complex preceding transacylation are indicative of the lower reactivity of thioester compounds compared with disulfide agents.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is interesting to note that only two molecules of the antiviral compound are required to completely inactivate one molecule of NCp7 as opposed to three molecules of disulfide based inhibitors (15,20,21) due to the lack of reactivity toward the aminoterminal zinc finger. Second, both the need for activation and the initial formation of a noncovalent complex preceding transacylation are indicative of the lower reactivity of thioester compounds compared with disulfide agents.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the dimeric cinnamate or salicylate structure as linked by disulfide bond may chelate zinc ion and may be necessary for MMP inhibition. 10,11) It should be noted that our compounds are different from the peptide-mimicking GM-1489, which displayed greater efficacy as MMP inhibitor. The difference in chemical structure suggests that our compounds and GM-1489 may have different action mechanism in inhibition of MMP activity.…”
Section: Cytotoxicity Of Synthetic Compoundsmentioning
confidence: 97%
“…9) Because the radical scavenging ability of mercaptans and disulfides is well-documented, we speculated that the introduction of these important functional groups into cinnamates or salicylates might yield potent antioxidants and UV protectants. In addition, we reasoned that the disulfides 10,11) and a-mercaptocarbonyl group 12) would chelate zinc ion at the active-site of MMP-1, which renders them to be potential MMP inhibitors. In this work, the sulfur-containing cinnamates and salicylates of substituted ester group were synthesized and the potency of these compounds as UV protective agents was evaluated by analyzing their free radical scavenging and for MMP-1 inhibitory activities.…”
mentioning
confidence: 99%
“…At least for the thioester zinc ejectors, nuclear magnetic resonance (NMR) and mass spectroscopy studies showed that they act by the covalent modification of Cys39 (20). Also, for DIBA compounds, the proposed reaction mechanism is a thiol-disulfide interchange between DIBA and NCp7 at Cys36 and Cys49 (23). We speculate that the N,NЈ-bis(1,2,3-thiadiazol-5-yl)benzene-1,2-diamine described here acts via a different mechanism, as its structural features do not allow an acyl transfer to Cys or a thiol-disulfide interchange.…”
Section: Discussionmentioning
confidence: 84%